Empathy Level vs. Coping with Difficult Social Situations among Children from General Education and Integrated Preschools - Papuda-Dolińska, Beata (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The article presents research on the level of empathy and coping skills in difficult social situations of 5-year-old non-disabled children attending general education and integrated preschools. Forty children were surveyed in each of such preschools. The purpose of the study was to determine the relationship between empathy conceptualized according to M. Hoffman?s sequential model and measured by EmQue questionnaire for parents by C. Rieffe, L. Ketelaar, C. H. Wiefferink and coping with difficult social situations in the ToPSS ? Taxonomy of Problematic Social Situations for Children by K.A. Dodge, C.L. McClaskey, E. Feldman (Polish adaptation by G. Szumski, J. Smogorzewska 2015). The second objective was to identify the differences between the examined groups of children in these two variables. Research has shown that the strongest predictor for coping with difficult social situations was the third level of empathy described as ?Prosocial Actions?. The more often children undertook prosocial actions, the less often they displayed difficulties in distinguished social situations. The study also confirmed the positive correlation of difficulty in responding to challenge with the first level of empathy, defined as ?Emotion Contagion?. Hypotheses about differences between the two groups have also been confirmed. Children from integrated preschools presented a higher level of empathy in its second and third level and better coped with the social situations.